King Lear - Shakespeare, William, 1564-1616 (Salt Lake City, UT : Project Gutenberg, 1997)
"King Lear" by William Shakespeare is a tragedy written in late 1605 or early 1606. Set in pre-Roman Britain, the play follows King Lear's catastrophic decision to divide his kingdom among his three daughters based on their declarations of love. When his youngest daughter refuses to flatter him, Lear sets in motion a chain of devastating consequences involving betrayal, madness, and blindness. Known for its dark tone and complex poetry, the play is regarded as one of Shakespeare's supreme achievements and among the greatest works of literature ever written. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/King_Lear
The First Folio, 1623
Release date is 1997-12-01
Keywords: Tragedies (Drama); Fathers and daughters -- Drama; Inheritance and succession -- Drama; Lear, King (Legendary character) -- Drama; Britons -- Drama; Kings and rulers -- Drama; Aging parents -- Drama